Investigating post-mortem redistribution of drugs in a cohort of suspected unnatural deaths in Cape Town South Africa - Clegg, Liza (Department of Pathology, 2025)
Introduction: The interpretation of post-mortem toxicological analysis results is complex, specifically, due to the phenomenon of post-mortem redistribution (PMR). The later needs to be taken into consideration when determining if, and to what extent a drug contributed to death. Additionally, case specific features also play a role and therefore no specific drug concentration can be deemed ‘fatal'. The accumulation of drugs in specific body areas before and around death creates drug reservoirs, influencing redistribution after death. However, patterns like concentration ratios between cardiac and peripheral blood aid in understanding PMR tendencies of specific drugs. By contributing data to the larger knowledge pool, we can better understand how different drugs behave in the post-mortem seeing, thereby assisting toxicologists and pathologists to come to a rational conclusion regarding the post-mortem toxicological results on a case-by-case basis. Methods: This study is the first of its kind in South Africa, aiming to investigate the extent of PMR of common drugs of use and misuse. To this end, paired admission femoral blood and autopsy femoral and cardiac blood samples were tested on a quantitative LC-MS/MS panel of 31 commonly misused drugs. Results: A total of 109 suspected unnatural cases admitted to the mortuary were included, of which 61 (56%) yielded positive toxicology results. The data was analysed using SPSS Version 28. The most common analytes detected were acetaminophen (n=13; 21.3%), 11-nor-9-carboxy-Δ⁹- tetrahydrocannabinol (THC-COOH) (n=20; 37.8%), amphetamine (n=30; 49.2%), methaqualone (n=33; 54.1%) and methamphetamine (n=33; 54.1%). Males represented the majority of cases in the cohort and the mean age of individuals testing positive was 33 years (SD: 10 years). Cardiac/peripheral (C/P) ratios were calculated and significant pairwise differences with Bonferroni correction were found for amphetamine, methamphetamine and nor-carboxy-tetrahydrocannabinol, corresponding with current literature. Additionally, where the literature was previously lacking data on the PMR of methaqualone, this study suggested that it is less likely to undergo PMR.